2023
DOI: 10.1186/s12969-023-00828-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the psychosocial factors associated with pain in children with juvenile idiopathic arthritis

Abstract: Background Pain is one of the most frequently reported experiences amongst children with Juvenile Idiopathic Arthritis (JIA); however, the management of JIA pain remains challenging. As pain is a multidimensional experience that is influenced by biological, psychological, and social factors, the key to effective pain management lies in understanding these complex relationships. The objective of this study is to systematically review the literature on psychosocial factors of children with JIA a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“…Further research should focus on how to identify patients who are at risk for chronic pain even after the inflammation is abrogated. When we are able to recognize children with chronic pain in an early stage, they might benefit from education about the cause of their pain, relevant pain mechanisms, and the role of psychosocial and physical factors in precipitating and maintaining chronic pain [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research should focus on how to identify patients who are at risk for chronic pain even after the inflammation is abrogated. When we are able to recognize children with chronic pain in an early stage, they might benefit from education about the cause of their pain, relevant pain mechanisms, and the role of psychosocial and physical factors in precipitating and maintaining chronic pain [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size of our study was limited, therefore more subtle differences might have been found in a larger study cohort. Second, pain is multifactorial in nature and affected by many psychosocial patient factors [ 39 ]. This study only looked at pain intensity and did not take a possible response shift during the study period into consideration [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The disease is also associated to a variety of negative outcomes (pain interference with physical, educational, emotional and social activities) [ 8 10 ]. JIA pain also affects patients psychosocially (sense of being misunderstood and stigmatize, overwhelming pain and despair, quality of life and mental health challenges) [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%